Long‐term effects of SARS‐CoV‐2 vaccination in the nursing home setting. Issue 5 (4th April 2022) - Rivasi, Giulia; Bulgaresi, Matteo; Bandinelli, Chiara; Balzi, Daniela; Tarantini, Francesca; Tognelli, Silvia; Lorini, Chiara; Buscemi, Primo; Baggiani, Lorenzo; Landini, Giancarlo; Ungar, Andrea; Bonaccorsi, Guglielmo; et al.
Abstract: Background: SARS‐CoV‐2 vaccination has significantly reduced infection, hospitalization, and lethality rates among nursing home (NH) residents, but durability of vaccine effects remains unknown. This study investigated the long‐term impact of BNT162b2 SARS‐CoV‐2 vaccine on breakthrough infection rates in the NHs of Florence, Italy. Methods: Participants included residents living in Florence NHs as of April 1st, 2021, who had completed the primary SARS‐CoV2 vaccination course by February 15th, 2021. Weekly rates of breakthrough infection were calculated between April 1st and October 31st 2021, with 7‐day incidence defined as the number of new confirmed SARS‐CoV‐2‐positive residents over the vaccinated resident census. Hospital admissions and deaths were recorded from local administrative and clinical sources. Patients admitted to NHs after April 1st were excluded to avoid confounding effect of different vaccination timing. Results: Among 2271 vaccinated residents (mean age 86.6, 74% female), we recorded 105 cases of breakthrough infections. Rates of breakthrough infection remained very low in the 6 months after vaccination, but started to rise over the following months, peaking at 0.94%, and then became stable around 0.2%–0.3%. Over the study period, infection rates remained low as compared to the incidence of SARS‐CoV‐2 infection during pre‐vaccination period. Overall hospitalization and lethality rates were 8%. Conclusions: Among vaccinated NH residents, rates of breakthrough SARS‐CoV‐2 infection, hospitalization and lethality remained low up to 9 months following primary vaccination course. A mild resurgence of SARS‐CoV‐2 infection, after 6 months from vaccination, suggests a decline of vaccine effectiveness in preventing transmission.